Analisis Tingkat Pemahaman Mahasiswa Terhadap Hukum Waris Islam: Studi Kasus Mahasiswa Semester III Angkatan 2021 Prodi Ilmu Hukum Universitas Islam Indragiri - Dea Maulana; Herdiansyah; Selma Ayu Lestari; M. Fajrin Gunawan (AL-BAHTS: Jurnal Ilmu Sosial,Politik, dah Hukum, 2024)
Islamic inheritance law is a part that is taught by Islam for all Muslims in the distribution of inheritance, but in reality there are still many Muslims who do not know or even study about it. Muslims now prefer to use customary law that has been in effect and developed in people's lives, it is rare to find the application of the distribution of Islamic inheritance law when dividing inheritance, this can be caused by a lack of knowledge and understanding of the rules and teachings of Islamic inheritance law. In this journal, the authors conducted research on the level of students' understanding of Islamic inheritance law in the Law Study Program, Faculty of Law, Indragiri Islamic University (UNISI) Semester III class of 2021. The purpose of this research, the authors expect students to understand the distribution of inheritance in Islam to avoid division or conflict between communities or families. In writing this article, the authors used a descriptive research method with a qualitative approach, by distributing questionnaires in the form of Google From to Law Faculty students class of 2021 semester III. In this study, the authors found the following conclusions: 1. Regarding students' understanding of inheritance law Islam reached 52.6%. 2. Regarding the importance for students to understand the law of inheritance to reach 100%. 3. Regarding Obstacles in studying Islamic inheritance law reaching 63.2%. 4. Regarding the level of understanding of students after attending the Islamic inheritance law course for 1 semester it reached 63.2%. 5. Regarding students' interest in Islamic inheritance law, it reached 78.9%. 6. Regarding the application of Islamic inheritance law in the family and surrounding community, it reaches 57.6%. 7. The most dominant applied in the distribution of inheritance is 78.9% Islamic inheritance law.